A governance of ion selectivity based on the occupancy of the "beacon" in one- and four-domain calcium and sodium channels - J. David Spafford (Taylor & Francis Group, 2023)
ABSTRACTOne of nature's exceptions was discovered when a Cav3 T-type channel was observed to switch phenotype from a calcium channel into a sodium channel by neutralizing an aspartate residue in the high field strength (HFS) +1 position within the ion selectivity filter. The HFS+1 site is dubbed a "beacon" for its location at the entryway just above the constricted, minimum radius of the HFS site's electronegative ring. A classification is proposed based on the occupancy of the HFS+1 "beacon" which correlates with the calcium- or sodium-selectivity phenotype. If the beacon is a glycine, or neutral, non-glycine residue, then the cation channel is calcium-selective or sodium-permeable, respectively (Class I). Occupancy of a beacon aspartate are calcium-selective channels (Class II) or possessing a strong calcium block (Class III). A residue lacking in position of the sequence alignment for the beacon are sodium channels (Class IV). The extent to which animal channels are sodium-selective is dictated in the occupancy of the HFS site with a lysine residue (Class III/IV). Governance involving the beacon solves the quandary the HFS site as a basis for ion selectivity, where an electronegative ring of glutamates at the HFS site generates a sodium-selective channel in one-domain channels but generates a calcium-selective channel in four-domain channels. Discovery of a splice variant in an exceptional channel revealed nature's exploits, highlighting the "beacon" as a principal determinant for calcium and sodium selectivity, encompassing known ion channels composed of one and four domains, from bacteria to animals.